Peculiarities of Future Educators’ Training for the Forming of the Fundamentals of National Consciousness in Children of Older Preschool Age - Marchii-Dmytrash, Tamara; Boryn, Halyna (Journal of Vasyl Stefanyk Precarpathian National University, 2023)
The peculiarities of professional training of future educators for the forming of older preschool-age children’s national consciousness are substantiated in the article. The main tasks, directions, and means of national education of children of older preschool age are analyzed. The main ethnographical means that contribute to the forming of the fundamentals of the national consciousness of children in the sixth year of life are specified and characterized, and the content of pedagogical activities aimed at expanding their horizons with specific ethnographical knowledge and ideas about important social phenomena and events is determined. All this can be realized with the help of various genres of oral folk art, traditions and customs of the Ukrainian people, folk games and toys, folk industries and crafts, and national symbols. All the ethnographical means listed above in figurative and rhythmic forms reflect real life in all its diversity (everyday life, social phenomena, work, human relationships) and contribute to national education, forming of the fundamentals of the national consciousness of older preschool-age children. It was established that preschool national education should help the child to form and apply the acquired social knowledge, and contribute to the forming of the skills of spiritual perception of national and cultural heritage. The result of national education should be reflected in the children's acquisition of social experience, the inheritance of the spiritual and moral values of the Ukrainian people, the achievement of a high level of national consciousness, as well as in the forming of a personality as a patriot of one's country. It is worth noting that national feelings are the basis of national consciousness and they do not arise by themselves, but only as a result of long-term educational influence on the personality, starting from the older preschool age. The future IPE teachers’ training for the development of national consciousness in children of older preschool age should be aimed at self-realization and the disclosure of their individual creative abilities. Gradually, the student’s vocabulary is enriched with everyday words, proverbs, sayings, tongue twisters, riddles, and other works of oral folk creativity, they learn to dramatize fragments of familiar Ukrainian fairy tales, make toys, decorate national dishes, clothes, and other household items. A systematic approach in work promotes the development of higher education getters’ interests in ethnography.